2013
DOI: 10.1371/journal.pone.0073785
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 and HDAC2 Restrain the Intestinal Inflammatory Response by Regulating Intestinal Epithelial Cell Differentiation

Abstract: Acetylation and deacetylation of histones and other proteins depends on histone acetyltransferases and histone deacetylases (HDACs) activities, leading to either positive or negative gene expression. HDAC inhibitors have uncovered a role for HDACs in proliferation, apoptosis and inflammation. However, little is known of the roles of specific HDACs in intestinal epithelial cells (IEC). We investigated the consequences of ablating both HDAC1 and HDAC2 in murine IECs. Floxed Hdac1 and Hdac2 homozygous mice were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
97
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 65 publications
9
97
0
5
Order By: Relevance
“…37,38 Treatment with rapamycin has been shown to inhibit the polyposis and progression to dysplasia induced by APC mutation. 25 Taken together, our studies and those of others 25,35,36 demonstrate the regulation of intestinal differentiation by mTORC1 signaling.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…37,38 Treatment with rapamycin has been shown to inhibit the polyposis and progression to dysplasia induced by APC mutation. 25 Taken together, our studies and those of others 25,35,36 demonstrate the regulation of intestinal differentiation by mTORC1 signaling.…”
Section: Discussionsupporting
confidence: 81%
“…36 Furthermore, dysregulated differentiation within the intestinal crypts is associated with the progression of colorectal cancer. 5 We previously demonstrated elevated mTOR activity and overexpression of mTOR complex components in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Do niche signals such as Wnt, therefore, play a role in maintaining an epigenetic state that dictates 'stemness' and do epigenetic mechanisms play a role in dedifferentiation? In the intestine the loss of histone deacetylase enzymes (HDAC1/2) disrupts cell lineage commitment [42]. A recent study on histone marks that permit chromatin accessibility surprisingly showed that many intergenic regulatory regions were prominently marked, with no significant differences, between intestinal stem cells and their progeny committed to the secretory and enterocyte lineages [43].…”
Section: Epigenetic Regulation Of Intestinal Plasticitymentioning
confidence: 99%
“…Commensal bacteriaderived signals also influence host epigenetic pathways, particularly through DNA and histone methylation [32][33][34][35][36] and histone acetylation and deacetylation [37][38][39][40][41] . The commensal microbiota produces multiple low-molecular-weight byproducts that modify the host cell epigenome and may alter the functional behavior of host cells.…”
Section: Special Issue (Mini Review) Gut Microbiota and Epigeneticsmentioning
confidence: 99%